ON GENERALIZATION OF SPECIAL FUNCTIONS RELATED TO WEYL GROUPS - Háková , Lenka; Háková , Lenka; Tereszkiewicz , Agnieszka (České vysoké učení technické v Praze, 2016)
Weyl group orbit functions are defined in the context of Weyl groups of simple Lie algebras. They are multivariable complex functions possessing remarkable properties such as (anti)invariance with respect to the corresponding Weyl group, continuous and discrete orthogonality. A crucial tool in their definition are so-called sign homomorphisms, which coincide with one-dimensional irreducible representations. In this work we generalize the definition of orbit functions using characters of irreducible representations of higher dimensions. We describe their properties and give examples for Weyl groups of rank 2 and 3.